دراسة الكفاءة الاقتصادية لإنتاج الفطر الزراعي في مشاريع صغيرة في سورية - يعقوب, غسان; حميدان, مروان; علي, غيث (Latakia University Journal -Biological Sciences Series, 2019)
هدفت الدراسة إلى تقييم ودراسة الكفاءة الاقتصادية لمزرعة فطر في سورية مساحتها 170م2 خلال حساب التكاليف والإيرادات, وباستخدام بعض المؤشرات الاقتصادية, حيث أظهرت النتائج ما يأتي: الربح السنوي الصافي = 397,490 ل.س. زمن استعادة رأس المال المستثمر = 3.85 سنة. معدل العائد الداخلي = 33.02%. إذا زراعة الفطر تحقق أرباحاً مضمونة وخلال فترة زمنية قصيرة, إذا ما توفرت الخبرة الفنية اللازمة ومستلزمات الإنتاج الأساسية التي تتمثل بشكل أساسي بتوفر الكمبوست (وسط الزراعة) الجيد المزروع بميسيليوم فطر عالي النقاوة ومن سلالة جيدة, وتأمين الشروط البيئية المناسبة, مع تأمين تسويق المنتج مباشرةً وبأسعار مناسبة لأنه محصول سريع العطب ولا يتحمل التخزين لمدة طويلة. لذلك توصي الدراسة بضرورة تشجيع ودعم مشاريع إنتاج الفطر في المناطق الريفية. The Purpose of this research is the evaluation and the study of economic efficiency for mushroom farm in Syria its survey 170 m2, taking in account the costs and returns, by using some of economic criteria, the results revealed: Net Annual Returns = 397,490 Syrian pounds. Recovery Time of Costs Investive = 3.85 year. Internal Rate of Return = 33.02%. So, the mushroom growing achieves absolute returns within a short period of time if we have the required technical experience, and a main production requirements, specially with the availability of a good compost which is seeded with high quality mycelium, and ensuring the perfect environmental conditions, and if the mushroom is marketed directly and with appropriate prices, because the yield is not able to be preserved for a long time. So, the study recommends the necessity of encouraging and supporting mushroom growing Enterprises in rural areas.